Growth dynamics of Celosia cristata grown in cocopeat, burnt rice hull and kenaf core fiber mixtures - Awang, Yahya; Shaharom, Anieza Shazmi; Mohamad, Rosli; Selamat, Ahmad (Science Publications, 2010)
Problem Statement: Understanding the growth dynamics of short-lived plant could be critical as it would complete its life cycle in a short time period. It does not normally has much time to adjust to hostile environmental condition. This study provides a detail account on growth dynamics of Celosia cristata grown in five growing media for the production of high quality flowers. Approach: Celosia cristata plants were grown on five growing media (v/v): 100% Cocopeat (CP); 70% CP: 30% Burnt Rice Hull (BRH); 70% CP: 30% perlite; 70% CP: 30% Kenaf Core Fiber (KCF) and 40% CP: 60% KCF. To explore the dynamics of plant growth and development, data on plant height and canopy diameter were regressed against Days After Transplanting (DAT) by using the equation y = A/(1+be-cx) while its derivative [dy/dx = (Abce-cx))/(1+be-cx)2] was used to estimate the growth rate of the parameter. The variation in leaf number, flower length and flower diameter were modeled using an exponential function of y = Aebx and their rate of change was derived using dx/dy = Abebx. Results: The growth rates of plant height, canopy diameter and leaf number of plants grown in media containing 100% CP, 70% CP: 30% BRH, 70% CP: 30% perlite, 70% CP: 30% KCF were higher than those grown on media containing 40% CP: 60% KCF. The growth rates of stem and canopy of the plants grown in the later media tended to be higher at the end of the growth cycle. This, however would not be sufficient to compensate their early losses, since the rate of growth in leaf number did not increase concurrently. Negative effects of media containing KCF were also detected in flower size. Conclusion: Overall results showed that CP is an excellent growing media for the production of Celosia cristata. Replacing 30% of CP with BRH, perlite and KCF did not affect the growth and flowering of the plants.